(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The analysis comprises a 33-day preparation period of the Polish representation in the ﬁ nale of the Team World Championships held in Chile (16 10—22 10 2001). Particular attention was focused on the time structure of ap- plied training — the arrangement and duration of mesocycles and microcycles. The second aspect of the performed analysis, which was of equal importance, was the general volume and proportions of the applied training means. The performed studies and an analysis of data available in literature indicated that rational preparation to the main start in tennis should comprise the following factors: 1) phase of long term preparations and the current acquired ﬁ tness level; 2) nature of preparations (orientation of workouts, type of applied means) as well as the values of basic parameters in training work (volume and intensity) that precede the particular period; 3) regularities connected with processes of restitution after diverse activities, as regards the magnitude (maximum, submaximal, average and small) and character of training load (related to speed, speed and strength, endurance, etc.); 4) the amount of time remaining for preparations to the main start. Keywords: structure of training, training mesocycles, training means.